2010
DOI: 10.2353/ajpath.2010.091204
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NURR1 as a Mediator of MIF Signaling During Chronic Arthritis

Abstract: Elucidation of factors regulating glucocorticoid (GC)sensitivity is required for the development of "steroid-sparing" therapies for chronic inflammatory diseases, including rheumatoid arthritis (RA). Accumulating evidence suggests that macrophage migration inhibitory factor (MIF) counterregulates the GC-induction of anti-inflammatory mediators, including mitogen-activated protein kinase phosphatase 1 (MKP1), a critical mitogen-activated protein kinase signaling inhibitor. This observation has yet to be extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…In addition, MIF displays a dominant role in diseases that are characterized by pro-inflammatory pathways, such as the severity of rheumatoid arthritis [20], cardiac dysfunction that is seen in sepsis [21], Crohn’s disease [22], and many different cancers [23-25]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, MIF displays a dominant role in diseases that are characterized by pro-inflammatory pathways, such as the severity of rheumatoid arthritis [20], cardiac dysfunction that is seen in sepsis [21], Crohn’s disease [22], and many different cancers [23-25]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that expression of the MAPK-regulating protein, MAPK phosphatase-1 (MKP-1) is inhibited by MIF (32, 54, 55), providing a potential mechanism to explain the effect of MIF deficiency on MAPK phosphorylation. In the present study, MKP-1 mRNA expression in unstimulated MIF −/− macrophages was significantly elevated relative to that in WT cells, an effect which could be eliminated by exposing the cells to recombinant MIF (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MKP-1 (also known as DUSP-1) belongs to the DUSP family, each member of which selectively de-phosphorylates various activated MAP kinases. DUSP-1 expression is inhibited by MIF in murine BMM and human synovial fibroblasts, facilitating MAPK activation[5,42]. Of note, multiple DUSPs are particularly involved in the regulation of ERK1/2 activity[43].…”
Section: Discussionmentioning
confidence: 99%